2014
DOI: 10.1186/1471-2164-15-402
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing on Solanum lycopersicum trichomes identifies transcription factors that activate terpene synthase promoters

Abstract: BackgroundGlandular trichomes are production and storage organs of specialized metabolites such as terpenes, which play a role in the plant’s defense system. The present study aimed to shed light on the regulation of terpene biosynthesis in Solanum lycopersicum trichomes by identification of transcription factors (TFs) that control the expression of terpene synthases.ResultsA trichome transcriptome database was created with a total of 27,195 contigs that contained 743 annotated TFs. Furthermore a quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 67 publications
2
114
0
Order By: Relevance
“…Arabidopsis plants exposed to whitefly feeding upregulate the transcription of both TPS10 and MYC2 ( Figure 2C; Supplemental Figure 6), suggesting that the Arabidopsis MYC2-TPS10 pathway is part of an induced defense against these insects. Furthermore, tomato Sl-MYC1, the homolog of At-MYC2, can transiently transactivate some potato (Solanum tuberosum) terpene synthase promoters in N. benthamiana leaves (Spyropoulou et al, 2014). We hypothesize that MYC2-TPS is a conserved element of plant resistance against whitefly infestation.…”
Section: Myc2-tps Is a Conserved And Efficient Defense Pathway Againsmentioning
confidence: 93%
“…Arabidopsis plants exposed to whitefly feeding upregulate the transcription of both TPS10 and MYC2 ( Figure 2C; Supplemental Figure 6), suggesting that the Arabidopsis MYC2-TPS10 pathway is part of an induced defense against these insects. Furthermore, tomato Sl-MYC1, the homolog of At-MYC2, can transiently transactivate some potato (Solanum tuberosum) terpene synthase promoters in N. benthamiana leaves (Spyropoulou et al, 2014). We hypothesize that MYC2-TPS is a conserved element of plant resistance against whitefly infestation.…”
Section: Myc2-tps Is a Conserved And Efficient Defense Pathway Againsmentioning
confidence: 93%
“…In Arabidopsis, it has been observed that the bHLH TF MYC2 directly binds sesquiterpene synthase gene promoters, resulting in an elevated release of volatile sesquiterpenes (Hong et al, 2012). Likewise, in tomato, a MYC-type bHLH and a WRKY TF have been described to bind the promoter of a sesquiterpene synthase gene (Spyropoulou et al, 2014). Finally, the bHLH TFs Bl and Bt from cucumber and BIS1 from C. roseus were recently identified as activators of the production of cucurbitane-type triterpenes and iridoid-type monoterpenes, respectively (Shang et al, 2014;Van Moerkercke et al, 2015).…”
Section: Members Of Clade Iva Of the Bhlh Family Activate Different Bmentioning
confidence: 99%
“…In fact, only a few TFs specifically modulating plant terpene biosynthesis have been identified in general. The basic helix-loop-helix (bHLH) TF MYC2, also known as a primary player in the JA signaling cascade (Kazan and Manners, 2013), and its homologs have been shown to play a role in the regulation of the biosynthesis of sesquiterpenes in Arabidopsis (Arabidopsis thaliana), tomato (Solanum lycopersicum), and Artemisia annua (Hong et al, 2012;Ji et al, 2014;Spyropoulou et al, 2014). Very recently, two other bHLH TFs, Bl (bitter leaf) and Bt (bitter fruit), not related to MYC2, were found to regulate the accumulation of cucurbitacin triterpenes in cucumber (Cucumis sativus; Shang et al, 2014).…”
mentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) TF MYC2 has emerged as a central regulator in JA signaling cascades, including those leading to the biosynthesis of several classes of specialized metabolites (9). MYC2-type TFs have been shown to be involved in the regulation of terpene biosynthesis genes in Arabidopsis thaliana, Artemisia annua (sweet wormwood), and Solanum lycopersicum (tomato) (10)(11)(12). In C. roseus, MYC2 regulates the expression of the ethylene response factor (ERF) Octadecanoid derivativeResponsive Catharanthus APETALA2-domain 3 (ORCA3) (13), the JA-inducible regulatory TF that modulates the JA-induced expression of the genes of the indole branch of the pathway, strictosidine synthase (STR), and several steps downstream of strictosidine, thereby controlling part of the JA-responsive production of MIAs (14,15).…”
Section: Significancementioning
confidence: 99%